Enasidenib vs conventional care in older patients with late-stage mutant-IDH2 relapsed/refractory AML: a randomized phase 3 trial - de Botton, S; Montesinos, P; Schuh, AC; Papayannidis, C; Vyas, P; Wei, AH; Ommen, H; Semochkin, S; Kim, H-J; Larson, RA; Koprivnikar, J; Frankfurt, O; et al. (American Society of Hematology, 2022)
This open-label, randomized, phase 3 trial (NCT02577406) compared enasidenib, an oral IDH2 (isocitrate dehydrogenase 2) inhibitor, with conventional care regimens (CCRs) in patients aged ≥60 years with late-stage, mutant-IDH2 acute myeloid leukemia (AML) relapsed/refractory (R/R) to 2 or 3 prior AML-directed therapies. Patients were first preselected to a CCR (azacitidine, intermediate-dose cytarabine, low-dose cytarabine, or supportive care) and then randomized (1:1) to enasidenib 100 mg per day or CCR. The primary endpoint was overall survival (OS). Secondary endpoints included event-free survival (EFS), time to treatment failure (TTF), overall response rate (ORR), hematologic improvement (HI), and transfusion independence (TI). Overall, 319 patients were randomized to enasidenib (n = 158) or CCR (n = 161). The median age was 71 years, median (range) enasidenib exposure was 142 days (3 to 1270), and CCR was 36 days (1 to 1166). One enasidenib (0.6%) and 20 CCR (12%) patients received no randomized treatment, and 30% and 43%, respectively, received subsequent AML-directed therapies during follow-up. The median OS with enasidenib vs CCR was 6.5 vs 6.2 months (HR [hazard ratio], 0.86; P = .23); 1-year survival was 37.5% vs 26.1%. Enasidenib meaningfully improved EFS (median, 4.9 vs 2.6 months with CCR; HR, 0.68; P = .008), TTF (median, 4.9 vs 1.9 months; HR, 0.53; P < .001), ORR (40.5% vs 9.9%; P <.001), HI (42.4% vs 11.2%), and red blood cell (RBC)-TI (31.7% vs 9.3%). Enasidenib safety was consistent with prior reports. The primary study endpoint was not met, but OS was confounded by early dropout and subsequent AML-directed therapies. Enasidenib provided meaningful benefits in EFS, TTF, ORR, HI, and RBC-TI in this heavily pretreated older mutant-IDH2 R/R AML population.